Portable Battery Charger Berbasis Sel Surya - Budhi Anto; Edy Hamdani; Rizki Abdullah (Universitas Syiah Kuala, 2014)
A type of solar battery charger is introduced in this paper. This equipment functions as a medium size rechargeable battery that is needed to move culinary merchants and coastal fishermen living in area which is not supplied by electrical networks. The equipment consists of solar module mounted onto portable mechanical construction, a 12-V 7.5-Ah lead acid battery and charge controller. Solar module charges the battery through charge controller and then the battery can be discharged to power on electric lamps for lightening culinary wagon or fisherman’s boat at night. Charge controller charges the battery with float charging which is implemented by maintaining 13.5 Volt between battery terminals and limiting the charging current to 1.5 Amperes. Charge controller circuit is based on adjustable linear voltage regulator LM338. The battery is of sealed lead acid type. This type of battery is maintenance free and more hygiene than other types of lead acid battery. The field experiment of charging the baterry of 50% residual capacity from 8 am to 4 pm under sunny weather shows that the solar module has charged the battery to its full capacity under battery safe charging conditions.Keywords: portable solar battery charger, float charging, LM338